Combined ablation for paroxysmal atrial fibrillation and drug-refractory hypertrophic obstructive cardiomyopathy: a case report. Issue 2 (8th February 2021) - Akita, Keitaro; Suwa, Kenichiro; Urushida, Tsuyoshi; Maekawa, Yuichiro
Abstract: Background: Hypertrophic obstructive cardiomyopathy (HOCM) is sometimes concomitant with atrial fibrillation (AF) and exacerbates heart failure symptoms. Although optimal medication for the reduction of left ventricular outflow tract (LVOT) obstruction and the maintenance of sinus rhythm should be considered, it is difficult to control the symptoms permanently. Case summary: A 45-year-old man, diagnosed with HOCM, presented with progressive dyspnoea on exertion, which significantly deteriorated during episodes of paroxysmal AF, despite optimal medical therapy. On echocardiography, we found LVOT obstruction with a peak pressure gradient of 98 mmHg, concomitant with redundant mitral valve leaflets, which caused significant systolic anterior motion (SAM). Since he declined open surgery, we selected a combination of catheter interventions, AF ablation, and alcohol septal ablation (ASA). After the AF ablation, the occurrence of AF significantly decreased, and there was no recurrence after the ASA. By 6 months, the plasma N-terminal pro-B-type natriuretic peptide level had decreased from 1022 to 124 pg/mL, the peak pressure gradient of LVOT decreased from 98 to 12 mmHg, and the left atrium volume decreased from 203 to 178.4 mL. The improvement in the SAM was visualized on echocardiography and was haemodynamically corroborated by the four-dimensional (4D)-flow cardiac magnetic resonance (CMR). Discussion: The treatment of drug-refractory HOCM concomitant with paroxysmal AF needs both septal reduction and the maintenance of sinus rhythm, which can be accomplished through transcatheter interventions. Moreover, the detailed intra-ventricular haemodynamic assessment in HOCM patients can be explored using the 4D-flow CMR.